2005
DOI: 10.17221/4011-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid contents and biological value of protein in various amaranth species

Abstract: Amino acid content before and after heat treatment was assessed in grain of six selected amaranth varieties and four species: Amaranthus cruentus, A. hypochondriacus, A. caudatus and A. hybridus, cultivated in the Czech Republic. High content of Lys and Arg was detected in both heat treated and untreated grains, as well as satisfactory content of Cys and lower levels of Met, Val, Ile and Leu. The latter three amino acids appear as limiting. Chemical scores of essential amino acids and essential amino acid inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 8 publications
2
33
0
4
Order By: Relevance
“…wheat (Müller, 1969) (Table 3); no significant differences were observed between raw and popped grain. In contrast, Gamel et al (2004) recorded the lowering of Tyr, Phe and Met levels due to popping, and Písaříková et al (2005) found a lower index of essential amino acids (EAAI) in popped grain compared to raw grain (85.4 vs. 90.4%).…”
Section: Resultsmentioning
confidence: 88%
“…wheat (Müller, 1969) (Table 3); no significant differences were observed between raw and popped grain. In contrast, Gamel et al (2004) recorded the lowering of Tyr, Phe and Met levels due to popping, and Písaříková et al (2005) found a lower index of essential amino acids (EAAI) in popped grain compared to raw grain (85.4 vs. 90.4%).…”
Section: Resultsmentioning
confidence: 88%
“…Whole egg protien was used as standard as reported by Block and Mitchell [1946] (Table 3). The Essential Amino Acid Index (EAAI) is a geometrical average of C S values [Písaříková et al 2005, Straková et al 2009]. The biological value of the experimental food materials was calculated from EAAI using Oser's [1959] method as:…”
Section: Methodsmentioning
confidence: 99%
“…Amaranth seeds may be processed for consumption in different ways and processing parameters may affect the oil. For instance, it was determined that the content of fat in selected varieties of A. cruentus, A. hypochondriacus, A. caudatus , and A. hybridus raw seeds was from 73.0 to 81.1 g/kg, whereas after popping, it slightly decreased and was 67.1 to 77.1 g/kg (Písaříková and others ). Bressani and others () observed a 3.9% reduction in the lipid content in A. caudatus seeds due to dry heating; however, possible reasons of such findings were not determined.…”
Section: Oil and Other Lipophilic Constituentsmentioning
confidence: 99%